Cancer Genetics and Epigenetics in Cancer Risk Assesment - Anna Meiliana; Nurrani Mustika Dewi; Andi Wijaya (Cell and BioPharmaceutical Institute, 2021)
Compared to the normal tissues, cancer cells tend to have higher proliferation rate and often lost their ability to undergo apoptosis. In addition, cancer cells can separate themselves from their original tissue thus causing metastasis in other part of body. While undergoing program cell death, disordered cellular programming can happen. The main causes of this cellular programming anomaly are epigenetic and genetic alterations, which have been known as two separate mechanisms in carcinogenetic. A recent outcome of whole exome sequencing of thousands of human cancers has been the unexpected discovery of many inactivating mutations in genes that control the epigenome. These mutations have the potential to disturb the DNA methylation patterns, histone modifications, and nucleosome positioning, hence, the causing gene expression alternation. Genetic alteration of the epigenome therefore contributes to cancer just as epigenetic process can cause point mutations and disable DNA repair functions. Epigenetic mechanisms changes could cause genetic mutations, and genetic mutations in epigenetic regulators could cause epigenome changes. Knowing that epigenome play a major role in the hierarchy of gene control mechanisms suggests that mutations might have impact on multiple pathways related to cancer phenotype. This pinpoint the fact that recently, the way the genes are organized and controlled are suggested to be a relevant factor for human carcinogenesis.Keywords: cancer genetic, cancer epigenetic, oncogens, tumor suppressor genes, driver mutation, passenger mutation